2017
DOI: 10.1016/j.ijppaw.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

From Galapagos doves to passerines: Spillover of Haemoproteus multipigmentatus

Abstract: Haemoproteus (Haemoproteus) multipigmentatus, a haemosporidian parasite thought to be specific to columbiform birds, was detected in passeriform birds on Santiago Island in the Galapagos archipelago. We surveyed birds along an altitudinal gradient on the islands of Santa Cruz, Isabela and Santiago between June 2013 and July 2015. Molecular screening of 2254 individuals from 25 species of endemic and introduced birds revealed clusters of passerine birds positive for H. multipigmentatus on Santiago Island that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The high prevalence and diversity of lineages found in louse flies suggest that this opportunistic feeding behavior is rather common. In addition, louse flies may be involved in the transmission of Haemoproteus parasites between distantly related species, as in the case of seabirds (i.e., frigatebirds) and passerines (Jaramillo et al, ; Santiago‐Alarcon et al, ). The alternative hypothesis, that louse flies are carried by migratory passerines, is unlikely to be the case, as this louse fly species, to the best of our knowledge, has not been recorded on any other bird species than the above‐mentioned Falco species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The high prevalence and diversity of lineages found in louse flies suggest that this opportunistic feeding behavior is rather common. In addition, louse flies may be involved in the transmission of Haemoproteus parasites between distantly related species, as in the case of seabirds (i.e., frigatebirds) and passerines (Jaramillo et al, ; Santiago‐Alarcon et al, ). The alternative hypothesis, that louse flies are carried by migratory passerines, is unlikely to be the case, as this louse fly species, to the best of our knowledge, has not been recorded on any other bird species than the above‐mentioned Falco species.…”
Section: Discussionmentioning
confidence: 99%
“…A newly colonized host represents a novel habitat for the parasite, and probably has a new blood cellular and immunological profile that may hamper the ability of the parasite to invade host cells, or result in the abortive development of the parasite at the tissue stage (Olias et al, ; Valkiūnas et al, ). For example, Jaramillo et al () found that H. multipigmentatus , which is a parasite that is thought to be specific to columbiform birds (Valkiūnas et al, ), was able to infect six different species of passerines that co‐occurred with the parasite's main host, i.e., the endemic Galapagos dove. However, despite a successful spillover from introduced rock pigeons ( Columba livia ) to doves and the subsequent spillover from doves to passerines, the absence of parasite gametocytes in passerine bird blood suggests that these are not competent hosts for this Haemoproteus lineage (Jaramillo et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We downloaded the ‘Hosts and Sites’ table from the MalAvi database (Bensch, Hellgren, & Pérez‐Tris, ) and filtered the dataset based on two specifications: (a) haemosporidians must have been recorded in at least 10 different host individuals, and (b) we only considered a haemosporidian species capable of infecting a host family if at least 10% of all documented infections for the parasite were found in that host family. We established these cut‐offs to increase the likelihood that we were analysing biologically meaningful host–parasite associations, as haemosporidians are known to occur as spillover infections into ‘dead‐end’ hosts (Jaramillo, Rohrer, & Parker, ; Moens et al, ), which can have a misleading effect if not removed.…”
Section: Methodsmentioning
confidence: 99%